An Overview of the Telfer 10 Mtpa Dump Leach Operation - Gelfi P; Mitchell I; Pyper R; Dunne R (The Australasian Institute of Mining and Metallurgy, 1994)
Dump leaching at Teller in its present form began in the fourth quarter of 1988 as an adjunct to milling operations. Initial plans called for a dedicated dump leach facility capable of processing ore at an annual rate of 2.0 million tonnes. Construction of a dump leach pad, collection and process ponds, carbon adsorption system, elution plant as well as reagent addition and ancillary facilities was initiated in mid-1988. During the course of construction, additional reserves were proven. As a result, design throughput was increased to 4.0 Mtpa. Leach pad capacity and solution supply systems were upgraded to handle the larger throughput. However, the carbon adsorption/elution facilities were not upgraded due to space limitations. During 1990 it was decided to expand the dump leach operation to 6.0 Mtpa. Construction of a second leach pad was required which was initiated in early-1991. Plans were again upgraded prior to completion to a target annual throughput of 10.0 million tonnes was. A further two leach pads have been constructed. The first of these being completed during the latter part of 1992. Construction of the latest and largest pad commenced early in 1994.